Romantic prose fiction - Gillespie, Gerald, 1933-; Engel, Manfred, 1953-; Dieterle, Bernard (Comparative history of literatures in European languages, 2008)
In this volume a team of three dozen international experts presents a fresh picture of literary prose fiction in the Romantic age seen from cross-cultural and interdisciplinary perspectives. The work treats the appearance of major themes in characteristically Romantic versions, the power of Romantic discourse to reshape imaginative writing, and a series of crucial reactions to the impact of Romanticism on cultural life down to the present, both in Europe and in the New World. Through its combination of chapters on thematic, generic, and discursive features, Romantic Prose Fiction achiev.